Physical activity and its determinant factors among medical students of Kerman University of Medical Sciences - Mina Danaei; Mohsen Momeni; Monavareh Sheikhshoaei; Ali Khalooei (Shahid Beheshti University of Medical Sciences, 2018)
Background: Exercise can play an important role in preventing chronic diseases. Given the key role of medical students on public health behaviors, the aim of the present study was to assess physical activity and factors influencing it in medical students of Kerman University of Medical Sciences.   Methods: The present cross-sectional study was conducted on 600 medical students of Kerman University of Medical Sciences, using census method, over a six-month period. The valid and reliable self-administrate international physical activity questionnaire was used. Relevant data were fed into IBM SPSS Statistics for Windows, Version 20.0. The data were analyzed using chi-square test, ANOVA and multinomial logistic regression.     Results: The level of physical activity was low in 275 (53.1%), moderate in 187 (36%), and vigorous in 57 (10.9%) of the participants. Students whose mothers or fathers had freelance jobs were 0.38 (P=0.005) or 0.54 (P=0.033) times less likely to have moderate physical activity compared with those whose mothers or fathers were retired. Students whose fathers had 'lower than diploma' education were 3.15 times more likely to have moderate physical activity (P=0.003). Comparing vigorous to low physical activities, students whose fathers were in governmental jobs were 3.15 times more likely to have vigorous physical activity (P=0.036). Also, students whose fathers had 'lower than diploma' education level were 0.17 times less likely to have vigorous physical activity (P=0.004).   Conclusion: Medical students in Iran are not in a good status in terms of physical activity. Considering the decisive role of parents in their children's attitudes towards physical activity, even in college, parent training seems necessary.